Attractive work and ergonomics: designing attractive work systems. (3rd July 2020) - Lööw, Joel
Abstract: Industrial organisations increasingly face problems with recruiting its workforce. Recent years have seen the most acute labour shortages. To overcome this challenge, organisations must provide work that is attractive to a new and wider workforce. This article thus argues that the task of designing attractive work systems should be a task of ergonomics. To this end, the article positions the notion of attractive work within sociotechnical systems theory. It then shows how current perspectives on attractive work, while important, do not address the complex issues of actually designing attractive work systems. In doing so, the article expands on sociotechnical systems theory and theories on attractive work to suggest a conceptualisation that allows for the understanding of the notion of attractive work with reference to different actors and their position in relation to the work system and socio-organisational context. The conceptualisation is then applied to a case from the mining industry to investigate its applicability. The analysis finds that designing attractive work systems necessitates a user-centric approach with a widened scope. Concern must include all users, even those who in fact will not directly use the designs. In short, a sensitivity to the larger society, the external environment, is needed.